AGENDA SETTING PORTAL BERITA CNN-LIVE NEWS DALAM PEMBERITAAN INVASI RUSIA KE UKRAINA - Verwis, Muhammad Siraj; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 2 (2023): Jurnal Ilmu Komunikasi Vol 4 No 2 Tahun 2023, 2023)
‘ The invasion of Ukraine by Russia’ at the end of February 2022 was enough to make the world uproar, this is certainly an interesting discussion for the media. This study aims to determine the Framing of news about the Russian lnvasion of Ukraine on February 24, 2022, in CNN Live News using Robert N. Entman's Framing analysis. This research uses a descriptive qualitative approach. The data source is obtained from the news released by CNN on February 24, 2022, about the Russian Invasion of Ukraine. The news published on February 24, 2022, was 171 news, the researchers took randomly, the first 2 news released on February 24, 2022, and the last 3 news released on February 24, 2022, in every 5 news. This was done to avoid bias. The method used in this research is ‘‘Robert Entman's Framing ’ analysis model which states that every media construct news must go through two stages, issue selection and aspect highlighting, after that, analyzing news with 4 stages, (1) define problems,-(2) diagnose causes,-(3) make moral judgments, and-(4) treatment recommendations. From the results of this study, CNN Live News does not frame its news in black and white. This is because, in its reporting, CNN only took Ukraine's point of view and interviewed sources who were pro-Ukraine, so it can be concluded that CNN framed Ukraine as a victim by providing news about Ukrainian citizens who panicked and also several major countries who spoke out, while Russia carried out attacks for no reason. KeyWord : Russian Invasion to Ukraine, CNN Live News, Framing